PROFIL KEMAMPUAN KOMUNIKASI MATEMATIS SISWA DALAM MENYELESAIKAN SOAL CERITA OPERASI HITUNG BENTUK ALJABAR KELAS VII SMP NEGERI 14 PALU: Profile of Students’ Mathematical Communication Skills in Solving Story Problems of Arithmetic Operations of Algebraic forms in Class VII SMP Negeri 14 Palu - Hikmah, Nurul; Hadjar, Ibnu (Universitas Tadulako, 2024)
This study aims to obtain a description of the profile of students' mathematical communication skills in solving story problems of arithmetic operations of algebraic forms in class VII SMP Negeri 14 Palu. This type of research is descriptive qualitative. The subjects in this study consisted of 3 students, 1 high ability student, 1 medium ability student, and 1 low ability student. Data collection techniques used tests and interviews. Data analysis was carried out using 3 stages, namely: data condensation, data presentation, and conclusion drawing. The results showed that high ability subjects achieved four indicators of mathematical communication ability in solving story problems of arithmetic operations of algebraic forms, medium ability subjects achieved four indicators of mathematical communication ability in solving story problems of arithmetic operations of algebraic forms but not all indicators could be explained verbally, and low ability subjects achieved three indicators of mathematical communication ability in solving story problems of arithmetic operations of algebraic forms and not all indicators could be explained verbally.